Perubahan Ekologis Pasca-Kebakaran di Kawasan Hutan Lindung Liang Anggang: Analisis Komprehensif tentang Kelangsungan Hidup Satwa dan Pemulihan Habitat - Shiba, Yasinta Nur; Rama, Juli; Fithria, Abdi; Satriadi, Trisnu (Fakultas Kehutanan Universitas Mulawarman, 2026)
Indonesia's peat swamp areas account for approximately 10.8% of the country's land area, with the Lianganggang Protected Forest in South Kalimantan being one of the key sites. Over-exploitation of peatlands leads to significant environmental impacts, such as forest fires, which alter forest structure and communities, thereby severely affecting wildlife populations. This study aims to evaluate the effects of forest and land fires on wildlife survival in the Lianganggang Protected Forest. Using a line transect observation method, both direct wildlife sightings and indirect signs such as footprints, feces, and sounds were monitored. The results revealed a notable decline in wildlife diversity, categorized into four types: birds, mammals, amphibians, and reptiles. In 2020, 40 bird species were observed, but only 15 remained by 2023. Mammal species dropped from 10 to 5, amphibians from 5 to 2, and reptiles from 5 to 3. These findings underscore the profound impact of forest fires on wildlife populations, highlighting the urgent need for effective conservation strategies to mitigate biodiversity loss.